Propane, n-butane and i-butane stabilization effects on methane gas hydrates. (December 2017) - Smith, Callum; Pack, David; Barifcani, Ahmed
Graphical abstract: Highlights: Analysis of increasing hydrate thermodynamic stability with propane, i-butane and n -butane addition to methane. Evaluation of structure II sensitivity of propane, i-butane and n -butane addition to methane. Dissociation enthalpy for propane, i-butane and n -butane in methane is related to composition. Hydrate-inert/promoting behaviour of propane, i-butane and n -butane in methane investigated. Abstract: The goal of this work is to analyse the hydrate equilibria of methane + propane, i-butane and n -butane gas mixtures. Experimental hydrate equilibrium data was acquired for various compositions of these components in methane, ranging from 0.5 to 6.8 mol%. Applying this information with the Clausius-Clapeyron equation, the extent of hydrate promotion was demonstrated quantitatively by calculating the slope of the equation and the dissociation enthalpy ( ΔHd ). Methane equilibria was found to be most sensitive towards propane and i-butane, where very small concentrations were sufficient to increase the thermodynamic conditions for hydrate equilibrium drastically. The degree of hydrate stabilisation, i.e. transition from sI to sII hydrate, was immediate – there was no detectable composition slightly above 0.0 mol% where propane or i-butane did not have a sII hydrate-promoting impact, although one was implied with the aid of Calsep PVTsim calculations. Addition of n -butane to methane was far less sensitive and was deemed inert from 0.0 to 0.5 mol%. It was concluded that the sII hydrate was favoured when the n -butane composition exceeded 0.5–0.75 mol%. The influence of composition on stability was quantified by determining the gradient of ΔHd versus mol% plots for the initial steep region that represents the increasing occupancy of the sII guests. Average gradients of 11.66, 26.64 and 43.50 kJ/mol.mol% were determined for n -butane, propane and i-butane addition to methane respectively. A hydrate-inert range for propane/i-butane (in methane) was suspected according to the perceived inflection point when less 0.5 mol%, implying the gradient was very low at some minute concentration range starting at 0.0 mol%. Awareness of these sI to sII transition regions is beneficial to natural gas recovery and processing as a small percentage of these components may remain without being detrimental in terms of promoting the hydrate equilibria.